Bahasa Inggris - Nur Anita (Faculty of Economics and Business, Jenderal Soedirman University, 2021)
This study aims to review the changes of Balanced Scorecard (BSC) approach over four generations followed by its research trends over the last three years. The narrative literature method is used to analyze the information of each reference. The last BSC generation generally is used by many companies caused it has been improved. Furthermore, the research trends currently show that the BSC is not only for profit-oriented entities but also for social companies. This study also found that there are many companies starting to combine BSC with other approaches. It is such as Best-Worst Method (BWM), Gray Relational Analysis, Data Envelopment Analysis, and SWOT analysis. By combining these approaches, the result of performance measurement will be more accurate.